A Rare Case of Cholecystitis Caused by Raoultella planticola. (29th May 2012) - Teo, Isabel; Wild, Jonathan; Ray, Saikat; Chadwick, David
Abstract : A 62-year-old female presented with right upper quadrant pain. Clinical examination and ultrasound scan were consistent with gallstones and acute cholecystitis. She received 3 days of intravenous Co-amoxiclav and was discharged with 5-days of oral antibiotics with arrangements to return for an elective cholecystectomy. This was performed 5 months later which revealed an inflamed gallbladder and a localised abscess secondary to gallbladder perforation. Fluid from the gallbladder was taken which cultured Raoultella planticola, a gram-negative, nonmotile environmental bacteria (Bagley et al. (1981)). This is the first report of biliary sepsis with a primary infection by R. planticola . This patient was treated with a 5-day course of oral Co-amoxiclav and made a full recovery.